Diálogos interculturais dentro de uma universidade brasileira - Figueiredo, Denise Miranda de (2013)
This doctoral thesis submitted to the Program of Postgraduate Studies in Clinical Psychology at the Catholic University of São Paulo aims to understand the unique experiences of displacement of college students to the capital city of São Paulo, from different regions of the African continent, enrolled in institutions of Higher Education. In this research we opted for a qualitative approach to present this as the most appropriate, since it is based on a paradigm that involves the human subjectivity, enabling participants to build relationships that allow greater access to the meanings of experiences for them. As a tool, we use the semi-structured interview, which allows the creation of a field in which conversational participants can bring their personal experiences, narrating them in a natural and peaceful form. To cope with this challenge, we interviewed six young men who live this experience. Two of these young people are from Angola, two from Guinea-Bissau, one student is Nigerian and another, from Cape Verde. In conducting the interview transcript we look at the recurring lines between the narratives of young people and the central themes that emerged them, thus guiding the construction of our categories and subcategories that were analyzed. Namely: Category I: My network in Africa; Where did I come from? Category II: Where am I? Who can I count on? Who do I think about? Category III: The Brazil experienced and the Brazil reported. Category IV: Prejudice and its different shades. And as subcategories: The difficult art of identifying veiled prejudice, ignorance reinforcing prejudice, blackness in Brazil and its impact on migration of young people, prejudice among Africans themselves and the different nuances of feeling alone. Category V: Marks imprinted by the migration experience